2016
DOI: 10.18632/oncotarget.9360
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 and platelet-rich fibrin enhance human breast adipose-derived stem cells function for soft tissue regeneration

Abstract: Adipose-derived stem cells (ASCs) can be used to repair soft tissue defects, wounds, burns, and scars and to regenerate various damaged tissues. The cell differentiation capacity of ASCs is crucial for engineered adipose tissue regeneration in reconstructive and plastic surgery. We previously reported that ginsenoside Rg1 (G-Rg1 or Rg1) promotes proliferation and differentiation of ASCs in vitro and in vivio. Here we show that both G-Rg1 and platelet-rich fibrin (PRF) improve the proliferation, differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Based on our previous studies, PRF is an excellent adjuvant for promoting the proliferation, differentiation, and paracrine function of ASCs [6]. In addition, functional optimization of NFSCs produced by PRF was also observed in this study (Figs.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Based on our previous studies, PRF is an excellent adjuvant for promoting the proliferation, differentiation, and paracrine function of ASCs [6]. In addition, functional optimization of NFSCs produced by PRF was also observed in this study (Figs.…”
Section: Discussionsupporting
confidence: 66%
“…The passaged cells grew markedly faster and reached the same confluence within 3 days compared with primary cells. All NFSC passages shared similar shapes and growth patterns with ASCs, which were obtained via the conventional collagenase digestion method described in our previous study [6]. After 2 weeks of inductive culture for adipocytes, osteoblasts, and chon-drocytes, positive staining for Oil Red O, alizarin red, and Alcian blue in cells indicated the multipotency of the NFSCs (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The implants were implanted in the subcutaneous environment and thus the ADSCs may have either secreted required growth factors to generate adipose tissue or differentiated into adipose tissue to form soft tissue. To date, minimal evidence has demonstrated the in-situ capacity of ADSCs to form adipose tissue without differentiation medium as shown in this study [39]. Fang-Tian et al demonstrated that ADSCs with PRP and ginsenoside Rg1 on collagen type I scaffolds could support adipocyte differentiation in vivo after 3 months of implantation in a nude mouse model [39].…”
Section: Discussionmentioning
confidence: 68%
“…To date, minimal evidence has demonstrated the in-situ capacity of ADSCs to form adipose tissue without differentiation medium as shown in this study [39]. Fang-Tian et al demonstrated that ADSCs with PRP and ginsenoside Rg1 on collagen type I scaffolds could support adipocyte differentiation in vivo after 3 months of implantation in a nude mouse model [39]. However, further studies are needed to understand the potential of ADSCs to form adipose in vivo without the supporting signals of differentiation medium.…”
Section: Discussionmentioning
confidence: 68%